Responses of Land-Use Changes to Drought and its Disparate Impact on Livelihoods of Farmers and Herders in the Agro-Pastoral Ecotone of Northwestern China - Zhang, Bailin; Ma, Ruiyang; Qu, Yanbo; Li, Yan; Jiang, Guanghui; Zhou, Jian (Frontiers in Environmental Science, 2022)
The agro-pastoral ecotone is an ecologically fragile region where drought is the main factor influencing land use and livelihoods. In this paper, we took two farmer villages and two herder villages in Ar Horqin Banner, located in the agro-pastoral ecotone of northwestern China, as the research areas, and where we conducted participatory rural appraisal and questionnaire survey to analyze the responses of land-use changes to drought and its disparate impact on the livelihoods of farmers and herders. Results show that: (1) Under drought, farmers tended to abandon rain-fed land, and herders tended to abandon grassland. (2) The livelihood activities of farmers were more stable than those of herders under drought. Farmers abandoned rain-fed farming, and herders just retained cattle rearing. The per capita net income of each farmer in Pingandi and Fenghuangling in the drought year of 2016 was only 9.27% and 12.52% lower than those in 2012, respectively, which was 132.88% and 128.25% lower than those in 2012 of each herder in Wuriduhubu and Haolibao. (3) Diversified livelihoods, especially non-agricultural ones, are the key to ensuring the sustainable livelihoods of farmers and herders. It is an effective way for farmers to encourage more labor force to emigrate to non-agricultural sectors. Regarding herders, it is urgent to develop artificial pastures and animal products processing industry with the support of government.